KETAHANAN HIDUP DAN PERTUMBUHAN NYAMUK Aedes spp PADA BERBAGAI JENIS AIR PERINDUKAN - Jacob, Aprianto; Pijoh, Victor D.; Wahongan, G. J. P. (e-Biomedik, 2014)
Abstract: In Indonesia there are two vectors are known, the main vector Aedes aegypti and Aedes albopictus as a potential vector, Aedes spp mosquito breeding varies but generally prefer clear water reservoirs. Eggs Aedes spp mosquitoes can hatch in the sewage, although not known survival and growth of larvae into pupae and adult mosquitoes. Objective: To determine the survival and growth of Aedes spp in various types of water breeding. Methods: Four types of breeding water taken directly from the settlement, and immediately used. Eggs Aedes spp laboratory strains incubated in water media. Larvae reared until the age of 4 days. A sample of 25 healthy larvae included six types of breeding water. The number of surviving larvae, pupae and adult mosquitoes be observed and counted every day for 15 days. Data security and growth of larvae processed manually in the form of percentages and graphs. Results: Aedes spp shown to survive in water dug wells (SGL), sewage water (sewer), as well as tap water. The presence of mosquitoes living in the sewer water can last up to 15 days with the same amount of mosquitoes from the first day until the last day. This phenomenon is different in the SGL and PAM water where mosquitoes can survive until day 15, although with a small percentage. Aedes spp proved unable to survive in wastewater soap. Conclusion: Water drains were left in place and clear become breeding places for Aedes spp good to note that its presence in the cleaning mosquito breeding. Keywords: The larvae of Aedes spp, life, death, pupa, adult mosquitoes, breeding water.     Abstrak: Di Indonesia dikenal ada dua vektor, vektor utama nyamuk  Aedes aegypti dan Aedes albopictus sebagaivektor potensial, perindukan nyamuk Aedes spp sangat bervariasi tetapi umumnya lebih menyukai tempat penampungan air jernih. Telur Aedes sppdapat menetas pada air comberan,meskipun belum diketahui ketahanan hidup dan pertumbuhan larva menjadi pupa dan nyamuk dewasa. Tujuan: mengetahui ketahanan hidup dan pertumbuhan nyamuk Aedes spp pada berbagai jenis air perindukan. Metode: Empat jenis air perindukan diambil secara langsung dari pemukiman penduduk dan langsung digunakan. Telur Aedes spp strain laboratorium ditetaskan pada media air bersih. Larva dipelihara hingga berumur 4 hari. Sampel sebanyak 25 ekor larva sehat dimasukkan ke enam jenis air perindukan. Jumlah larva yang bertahan hidup, menjadi pupa dan nyamuk dewasa diamati dan dihitung setiap hari selama 15 hari. Data ketahanan dan pertumbuhan larva diolah secara manual dalam bentuk persentase dan grafik. Hasil: Nyamuk Aedes spp terbukti dapat bertahan hidup pada air sumur gali (SGL), air comberan (got), serta air PAM.  Keberadaan nyamuk hidup pada air got  mampu  bertahan  sampai 15 hari dengan jumlah nyamuk yang sama dari hari pertama sampai hari terakhir. Fenomena ini berbeda pada air SGL dan PAM dimana nyamuk mampu bertahan sampai hari ke-15 meskipun dengan persentase kecil. Nyamuk Aedes spp terbukti tidak dapat bertahan hidup pada air limbah sabun. Simpulan:  Air got yang didiamkan dan jernih menjadi tempat perindukan yang baik bagi Aedes spp sehingga keberadaannya perlu diperhatikan dalam pembersihan sarang nyamuk. Kata kunci: Larva Aedes spp, hidup, mati, pupa, nyamuk dewasa, air perindukan.